Research and development in quality of service multicast routing in MANET - Soong, Boon Hee. (2008)
This report summarizes the main research work during the past three and a half years of the project undertaken at Positioning & Wireless Technology Centre (PWTC) of NTU. It covers the following research topics: centralized multi-constrained Quality of Service (QoS) routing algorithms, MANET test-bed developments, QoS routing protocol for multi-cluster based ad hoc network with mobile backbone, QoS multicast routing protocol for multi-cluster based mobile ad hoc network (MANET), and hierarchical routing algorithms for large scale road networks. For the centralized multi-constrained QoS routing problem, by keeping limited number of non-dominated paths in each node according to a nonlinear path function, we have proposed Limited Path Dijkstra’s Algorithm (LPDA) and the Improved Limited Path Heuristic Algorithm (ILPHA). It is shown that our ILPHA improves the previous Limited Path Heuristic Algorithm (LPHA) significantly, and the heuristic algorithms with dominating area non-linear path function outperform the heuristic algorithms with the max weight based non-linear path function. For MANET test-bed developments, our practices in two MANET test-beds for video conference and video surveillance will be given, their implementation architecture and their notable features will be introduced. MANET addresses challenging QoS routing problem, particularly when the network is in large scale. We have studied the ad hoc network with Mobile Backbones (MBN) and this report introduces our findings for design of a hybrid QoS routing protocol for MBN. It is based on a proactive Intra-group Link state Updating Protocol (ILUP) and reactively discovery multiple segmented QoS paths sequentially from the source to the destination. The route search algorithm is modified from the k-shortest path algorithm or the Limited Path Dijkstra’s Algorithm (LPDA). Simulation results show the efficiency of the proposed protocol.